ANALYSIS OF THE USE ACTIVITY BASED COSTING IN DETERMINING TUITION FEES - Fasa, Azmi (UIN Sunan Gunung Djati Bandung, 2024)
Numerous educational institutions in Indonesia suffer financial deficits, negatively impacting educational quality. This study aims to ascertain the Tuition Fees at Nurul Fajri Islamic Boarding School Majalengka utilizing the Activity-Based Costing (ABC) method. It investigates the application of the ABC method in determining Tuition Fees within educational foundation institutions, a novel approach, particularly for pesantren foundations. The research adopts a qualitative methodology with a problem-focused approach. Data collection involved interviews and an analysis of pertinent financial and operational documents. Cost activity data was processed using ABC costing, resulting in tuition fees calculations based on the ABC method. These calculations were then juxtaposed with the Tuition Fees Â established by the school administration. The analysis identified a cost discrepancy (undercharging), where the cost per student exceeded the total Tuition Fees income and School Operational Funds (SOF) or Government Subsidy. For junior high school grades 1, 2, and 3, the differences were Rp 68,092, Rp 65,877, and Rp 85,668, respectively. For high school levels 1, 2, and 3, the discrepancies were Rp 6,674, Rp 49,014, and Rp 51,354, respectively. The study recommends that the school increase the monthly tuition fees to adequately cover the actual costs of education.